Market Intervention Policy in The Case of Rising Rice Prices in Indonesia From The Perspective of Ibn Taimiyah - Bella, Alif Mujiyana Eka; Rahmawati, Lilik; Jim, Mahafizur Rahman (Universitas Muhammadiyah Surakarta, 2024)
Rice is an important commodity and is needed by the wider community, its existence is vital as a means to fulfil the needs of life, therefore the Indonesian government's intervention in this commodity is very high. The price of rice in Indonesia continues to rise for many factors. This research employs qualitative methods which is called library research. The result of this study is the increase in rice prices in Indonesia according to Ibn Taymiyyah is entirely caused by market forces. According to Ibn Taymiyyah what is needed therefore is market intervention, instead of price intervention. The market intervention carried out by the Indonesian government is by intensifying the social assistance program, running market operations with the SPHP program, and strengthening the stock of government rice reserves (CBP). Meanwhile, the policy of setting the price ceiling should not be carried out by the government because the market conditions related to this rice commodity run perfectly and there is no market distortion.